From poverty to trust: Political implications of the anti-poverty campaign in China. Issue 2 (March 2023) - (Vera) Zuo, Cai; Wang, Zhongyuan; Zeng, Qingjie
Despite the rapid decrease in poverty across the developing world, there have been few attempts to analyze the implication of poverty alleviation on regime legitimacy. Bridging the literature on poverty alleviation and political trust, this analysis examines the mechanisms through which poverty reduction affects trust in local elected and appointed officials. Using an original survey on the Target Poverty Alleviation campaign in China and causal mediation analyses, we find that beneficiary status is positively associated with political trust. The perception of anti-poverty governance quality, rather than economic evaluation, is the mediator through which beneficiary status affects political trust. Moreover, the intensified non-formalistic elite-mass linkage developed in the poverty alleviation campaign enhances political trust through the improvement of perception of governance quality. These findings have implications for mechanisms through which poverty reduction affects political trust and the type of political linkage that sustains regime legitimacy.